Encoding the Discipline: English Graduate Student Reflections on Working with TEI - Maura Ives; Victor Del Hierro; Bailey Kelsey; Laura Catherine Smith; Christina Sumners (Journal of the Text Encoding Initiative)
Students in two graduate English seminars at Texas A&M were offered an introduction to TEI encoding and were surveyed as to their experiences. Four students presented short papers to the TEI meeting that incorporated both the survey responses and their own perspectives as relative newcomers to TEI. These papers demonstrate why it is important to incorporate TEI in the graduate curriculum, how that incorporation might best be approached, and what happens when TEI is viewed through a disciplinary lens.